Resposta :
Resposta:
(a,b) = (0,-20)
Explicação
a10+10= 20
b)10-10=0
ai os dois resultados vão ficar assim (a,b)=(0,-20)
Explicação passo-a-passo:
[tex]a = 10 + 10 + b = 10 - 10 \\ a = 10 - 10 \\ 10 + 10 + b = 10 - 10 \\ a = 10 - 10 \\ a = 0 \\ a = 10 - 10 \\ 10 + 10 + b = 10 - 10 \\ a = 0 \\ 10 + 10 + b = 10 - 10 \\ 10 + b = - 10 \\ b = - 10 - 10 \\ b = - 20 \\a =10 - 10 \\ 10 + 10 + b = 10 - 10 \\ a = 0 \\ b - 20 \\ (a.b) = 0. - 20 \\ 0 = 10 + 10 + ( - 20) = 10 - 10 \\ 0 = 0 = 0 \\ (a.b) = (0. - 20) \\ resposta \\ (a.b) = (0. - 20)[/tex]